Difficulties and Challenges in Implementation Process of EU Projects in Croatia - Marko Šostar; Ines Čevapović (European Scientific Journal, ESJ, 2017)
After the process of application to different funds, and upon the approval of the project, many institutions and organizations encounter unexpected situations of implementation difficulties. Starting with the fact that those institutions and organizations are full of ideas for implementing their goals and objectives, and the only factor standing between them and their results is the lack of funds, gain of those funds seems as a full green light for accomplishing what they imagined and worked on. But after the notice of approved funding, they are stepping into a complicated web of problems they often do not expect and face situations which make it impossible to implement their planned activities. Even though the funds are approved, beneficiaries will soon begin to realize that the access to those funds is far from reach. Most of activities will again depend of the financial resources of the organization on its own, which will put enormous risk on the implementation itself. Financial difficulties are the ones that are always felt the most, but other problems that will appear suddenly during the preparation of activities will show to be also very hard to manage, such as institutional, legislation and project problems. Each group of problems will demand full attention of the manager and participation and cooperation of a wider group of subjects connected to the implementation process depending on the nature of the problem. Article will categorize the problematics and explore the experiences of Croatian project managers coping with problems in their work according to statistical results gathered through an on-line survey. The research was performed in June and July 2016 and reached a span of 50 Croatian project managers